Ha Hoang
Vài giây trước

\(12a^2b\left(a-b\right)\left(a+b\right)\)

\(=12a^2b\left(a^2-b^2\right)\)

\(=12a^4b-12a^2b^3\)

Bình luận (0)
OH-YEAH^^
2 phút trước

1c) Ta có: \(\widehat{A}+\widehat{B}+\widehat{E}+x=360^0\)

\(65^0+90^0+90^0+x=360^0\)

\(245^0+x=360^0\)

\(x=360^0-245^0\)

\(x=115^0\)

Bình luận (0)
ngọc quỳnh
7 phút trước

giúp mik với mn mik cần rất gấp

 

Bình luận (0)
Lấp La Lấp Lánh
5 phút trước

a) \(P=A:B=\left(\dfrac{\sqrt{x}}{\sqrt{x}-1}-\dfrac{1}{x-\sqrt{x}}\right):\dfrac{\sqrt{x}+1}{x-1}\left(đk:x>0,x\ne1\right)\)

\(=\dfrac{x-1}{\sqrt{x}\left(\sqrt{x}-1\right)}.\dfrac{x-1}{\sqrt{x}+1}=\dfrac{\left(x-1\right)^2}{\sqrt{x}\left(x-1\right)}=\dfrac{x-1}{\sqrt{x}}\)

b) \(P\sqrt{x}=m+\sqrt{x}\)

\(\Leftrightarrow\dfrac{x-1}{\sqrt{x}}.\sqrt{x}=m+\sqrt{x}\)

\(\Leftrightarrow x-1=m+\sqrt{x}\)

\(\Leftrightarrow m=x-\sqrt{x}-1\)

Bình luận (0)

Khoá học trên OLM của Đại học Sư phạm HN